Stem Cell-Based Therapy for Spinal Cord Injury - Vladislav Volarevic; Slaven Erceg; Shom Shanker Bhattacharya; Petra Stojkovic; Philip Horner; Miodrag Stojkovic (Cell Transplantation, 2013)
Stem cells (SCs) represent a new therapeutic approach for spinal cord injury (SCI) by enabling improved sensory and motor functions in animal models. The main goal of SC-based therapy for SCI is the replacement of neurons and glial cells that undergo cell death soon after injury. Stem cells are able to promote remyelination via oligodendroglia cell replacement to produce trophic factors enhancing neurite outgrowth, axonal elongation, and fiber density and to activate resident or transplanted progenitor cells across the lesion cavity. While several SC transplantation strategies have shown promising yet partial efficacy, mechanistic proof is generally lacking and is arguably the largest impediment toward faster progress and clinical application. The main challenge ahead is to spur on cooperation between clinicians, researchers, and patients in order to define and optimize the mechanisms of SC function and to establish the ideal source/s of SCs that produce efficient and also safe therapeutic approaches.